A direct and efficient 3-halooxidation of indoles using DMSO as oxygen source. (3rd March 2023) - Zheng, Tao; Li, Zhiqun; Luo, Yuling; Zhang, Jingjie; Xu, Jun
Abstract: Here we develop a direct and efficient protocol for 3-halooxidation of indoles using DMSO as the oxygen source and NXS (X = Br, Cl) the halo source. This protocol features broad substrate scope and good to excellent yields, thus rendering it as a highly versatile, straightforward, and atom-economical alternative prior to the previously reported methods, which possess their capability to undergo the SN 1 substitution of a highly reactive electrophilic o -azaxylylene intermediate to generate 3, 3-disubstituted oxindoles. Graphical abstract: Image 1